A Highly Translatable Dual‐arm Local Delivery Strategy To Achieve Widespread Therapeutic Coverage in Healthy and Tumor‐bearing Brain Tissues. Issue 11 (17th January 2023) - Negron, Karina; Kwak, Gijung; Wang, Heng; Li, Haolin; Huang, Yi‐Ting; Chen, Shun‐Wen; Tyler, Betty; Eberhart, Charles G.; Hanes, Justin; Suk, Jung Soo
Abstract: Drug delivery nanoparticles (NPs) based entirely on materials generally recognized as safe that provide widespread parenchymal distribution following intracranial administration via convection‐enhanced delivery (CED) are introduced. Poly(lactic‐co‐glycolic acid) (PLGA) NPs are coated with various poloxamers, including F68, F98, or F127, via physical adsorption to render particle surfaces non‐adhesive, thereby resisting interactions with brain extracellular matrix. F127‐coated PLGA (F127/PLGA) NPs provide markedly greater distribution in healthy rat brains compared to uncoated NPs and widespread coverage in orthotopically‐established brain tumors. Distribution analysis of variously‐sized F127/PLGA NPs determines the average rat brain tissue porosity to be between 135 and 170 nm while revealing unprecedented brain coverage of larger F127/PLGA NPs with an aid of hydraulic pressure provided by CED. Importantly, F127/PLGA NPs can be lyophilized for long‐term storage without compromising their ability to penetrate the brain tissue. Further, 65‐ and 200‐nm F127/PLGA NPs lyophilized‐reconstituted and administered in a moderately hyperosmolar infusate solution show further enhance particle dissemination in the brain via osmotically‐driven enlargement of the brain tissue porosity. Combination of F127/PLGA NPs and osmotic tissue modulation provides a means with a clear regulatory path to maximize the brain distribution of large NPs that enable greater drug loading and prolong drug release. Abstract : Poloxamer F127‐coated biodegradable nanoparticles (NPs) provide widespread distribution in healthy and tumor‐bearing brain tissues following intracranial convection‐enhanced delivery and the administration in a hyperosmolar infusate solution further augments the NP distribution. F127‐coated biodegradable NPs and osmotic brain extracellular modulation combine to maximize the therapeutic coverage of larger NPs that enable greater drug loading capacity and sustained drug release kinetics.